Olivi's Peaceable Kingdom : a Reading of the Apocalypse Commentary - Burr, David (The Middle Ages Series, 2016)
Everyone who knows anything at all about Petrus Iohannis Olivi knows that his Apocalypse commentary was censured; yet opinions on that condemnation vary. The basic facts are clear. After Olivi's death in 1298, his writings were suppressed by the Franciscan order, yet his tomb at Narbonne became such a popular pilgrimage site that by the second decade of the fourteenth century the crowds were said to rival those a the Porziuncula in Assisi. In 1318 Olivi's body was unobtrusively exhumed and removed to an undisclosed location. The attacks on Olivi had come to concentrate on this Revelation commentary, and with good reason. The spirituals found it increasingly relevant to their situation. By 1318 John had ordered an investigation which led to the report of an eight-man commission in 1319. He then submitted particular passages from Oivi's commentary to individual theologians before he himself condemned it in 1326. Those are the facts. In this book David Burr reconsiders their significance.